Mutated IKZF1 is an independent marker of adverse risk in acute myeloid leukemia - Eckardt, Jan-Niklas; Stasik, Sebastian; Röllig, Christoph; Petzold, Andreas; Sauer, Tim; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Brümmendorf, Tim Henrik; Naumann, Ralph; Steffen, Björn; Kunzmann, Volker; et al. (Leukemia, 2023)
Genetic lesions of IKZF1 are frequent events and well-established markers of adverse risk in acute lymphoblastic leukemia. However, their function in the pathophysiology and impact on patient outcome in acute myeloid leukemia (AML) remains elusive. In a multicenter cohort of 1606 newly diagnosed and intensively treated adult AML patients, we found IKZF1 alterations in 45 cases with a mutational hotspot at N159S. AML with mutated IKZF1 was associated with alterations in RUNX1, GATA2, KRAS, KIT, SF3B1, and ETV6, while alterations of NPM1, TET2, FLT3-ITD, and normal karyotypes were less frequent. The clinical phenotype of IKZF1-mutated AML was dominated by anemia and thrombocytopenia. In both univariable and multivariable analyses adjusting for age, de novo and secondary AML, and ELN2022 risk categories, we found mutated IKZF1 to be an independent marker of adverse risk regarding complete remission rate, event-free, relapse-free, and overall survival. The deleterious effects of mutated IKZF1 also prevailed in patients who underwent allogeneic hematopoietic stem cell transplantation (n = 519) in both univariable and multivariable models. These dismal outcomes are only partially explained by the hotspot mutation N159S. Our findings suggest a role for IKZF1 mutation status in AML risk modeling.
Online veröffentlicht: 13. Oktober 2023
Gesehen am 29.01.2024